Genetic diversity among farmer-preferred cassava landraces in Uganda - Turyagyenda, L.F.; Kizito, Elizabeth Balyejusa; Ferguson, Morag E.; Baguma, Yona K.; Harvey, Jagger J.W.; Gibson, P.J.; Wanjala, Bramwel W.; Osiru, D.S.O. (2012)
Understanding of genetic diversity among a breeding population is an important requirement for crop improvement as it allows for the selection of diverse parental combinations and formation of heterotic pools for genetic gain. This study was carried out to determine genetic diversity within and among 51 farmer-preferred cassava (Manihot esculenta) landraces and 15 elite accessions grown in Uganda. Twenty six simple sequence repeat (SSR) markers used for genetic diversity assessment in this study revealed a total of 154 alleles, of which 24% were unique alleles present only in landraces. The genetic diversity and observed herozygosity in landraces were slightly higher than in elite accessions. Elite accessions clustered with some of the landraces indicating that there were some alleles in common. However, 58.8% of the landraces fell into 3 different clusters independent of the elite accessions. Including these landraces with unique alleles in cassava breeding schemes will increase the chances of producing farmer preferred adapted elite cultivars. The study also revealed genetic differentiation among accessions from different regions providing an opportunity for establishment of heterotic pools within a breeding programme.